Teaching Methodology of Computer Science in General Education Schools - Kozimjan kizi , Erkinova Odinakhan (Miasto Przyszłości, 2023)
This article examines the methods and science of informatics and explains the nature of the subject to students. Up to now, informatics is taught as the main subject in the higher education system.